2008
DOI: 10.1111/j.1471-4159.2008.05407.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and clearance of α‐synuclein aggregates demonstrated by time‐lapse imaging

Abstract: 1Authors share senior authorship.Abbreviations used: 3MA, 3-methyladenine; ALLN, N-acetyl-leucylleucyl-norleucinal; EGFP, enhanced green fluorescent protein; PD, Parkinson's disease; WT, wildtype; DC, C-terminally truncated a-synuclein consisting of amino acids 1-108. AbstractAggregates of a-synuclein are the pathological hallmark of sporadic Parkinson's disease (PD), and mutations in the a-synuclein gene underlie familial forms of the disease. To characterize the formation of a-synuclein aggregates in living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
97
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 41 publications
8
97
0
1
Order By: Relevance
“…It is known that overexpression of a-Syn leads to formation of a specific type of inclusions termed aggresome, which is uniquely located in the vicinity of the centrosome and assembled by retrograde transport of dynein motors along the microtubule network (Opazo et al, 2008;Tanaka et al, 2004). Consistently, these perinuclear structures were enriched with vimentin, a known aggresome marker that displayed homogeneous distribution in cells without aggresome formation (Fig.…”
supporting
confidence: 56%
“…It is known that overexpression of a-Syn leads to formation of a specific type of inclusions termed aggresome, which is uniquely located in the vicinity of the centrosome and assembled by retrograde transport of dynein motors along the microtubule network (Opazo et al, 2008;Tanaka et al, 2004). Consistently, these perinuclear structures were enriched with vimentin, a known aggresome marker that displayed homogeneous distribution in cells without aggresome formation (Fig.…”
supporting
confidence: 56%
“…In addition, since specks highly resemble perinuclear structures called aggresomes (Opazo et al, 2008), we examined ASC specks for the expression of several markers of aggresome formation. Aggresomes are large perinuclear collections of misfolded proteins that dynamically form and are subsequently dismantled by lysosomes during autophagy (Opazo et al, 2008).…”
mentioning
confidence: 99%
“…Following the discovery that Hsp70 can abrogate the neurotoxicity of abnormal polyglutamine proteins (Warrick et al, 1999), it was shown that Hsp70 can also prevent dopaminergic neuronal loss associated with αSyn in a Drosophila PD model (Auluck et al, 2002). Numerous studies that followed have reported that over-expression of Hsp70 is able to reduce αSyn aggregation and/or toxicity in various cellular models Klucken et al, 2004b;McLean et al, 2004;Opazo et al, 2008;Outeiro et al, 2008;Zhou et al, 2004). In particular, McLean and co-workers (Outeiro et al, 2008) have found that Hsp70 rescues αSyn-linked toxicity by promoting the cellular clearance of αSyn oligomers, rather than monomers.…”
Section: Hsp70 In Modulation Of αSyn Aggregation and Cytotoxicitymentioning
confidence: 99%
“…In particular, McLean and co-workers (Outeiro et al, 2008) have found that Hsp70 rescues αSyn-linked toxicity by promoting the cellular clearance of αSyn oligomers, rather than monomers. Another study (Opazo et al, 2008) found that Hsp70 manages αSyn intracellular aggregation by increasing the clearing of aggregates primarily through the aggresome, and the subsequent removal of small aggregates and aggresomes from the cytosol. An interesting study by McLean and colleagues has recently shown that Hsp70 can also inhibit the formation of extracellular αSyn oligomers and rescue the cytotoxicity produced by such secreted oligomers, in a cellular model.…”
Section: Hsp70 In Modulation Of αSyn Aggregation and Cytotoxicitymentioning
confidence: 99%